Living under their boats: a strategy for southern sealing in the nineteenth century – its history and archaeological potential. Issue 1 (2nd January 2018) - Pearson, Michael
Abstract: During the nineteenth century, sealers working in the Southern Ocean around Antarctica had several strategies for gathering seal skins and oil. Where seals were abundant and a long period ashore was required to exploit them, a stone shelter was often constructed or a cave was occupied. Where fewer seals were seen, and where accessible beaches were very small, sealers went ashore by whale boat and slept under the upturned boat for the short period needed to kill the seals. Living under upturned boats was also a practice used by crews of wrecked sealing ships; boats provided short-term shelter in emergencies, and also when sealers travelled to secure food or other resources to survive. The paper looks at the background of this strategy, the historical sources describing life under the boats and the experiences of the sealers involved. It then uses a series of models to hypothesise what the archaeological evidence of boat camps might look like. Finally, this paper describes two archaeological sites in the South Shetland Islands that display characteristics of boat camps, and suggests that further surveys for boat camp sites in the Antarctic and sub-Antarctic regions are needed in future.